Effectiveness and safety of manual therapy for knee osteoarthritis: An overview of systematic reviews and meta-analyses - Feng, Tianxiao; Wang, Xu; Jin, Zikai; Qin, Xiaokuan; Sun, Chuanrui; Qi, Baoyu; Zhang, Yili; Zhu, Liguo; Wei, Xu (Frontiers in Public Health, 2023)
Background Manual therapy has been used as an alternative approach to treat knee osteoarthritis (KOA) for many years. Numerous systematic reviews (SRs) or meta-analyses (MAs) were published to evaluate its effectiveness and safety. Nevertheless, the conclusions of SRs/MAs are inconsistent, and the uneven quality needs to be critically appraised. Objectives To conduct a comprehensive overview of the effectiveness and safety of manual therapy for KOA and the quality of relevant SRs/MAs, thus providing critical evidence and valuable direction for future researchers to promote the generation of advanced evidence. Methods The pre-defined search strategies were applied to eight electronic databases from inception to September 2022. Suitable SRs/MAs were included in accordance with the inclusion and exclusion criteria. The methodological quality, risk of bias, reporting quality, and evidence quality were assessed by two independent reviewers who used respectively the A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic Reviews (ROBIS), the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 Version (PRISMA 2020), and Grades of Recommendations, Assessment, Development and Evaluation (GRADE) based on the method of narrative synthesis. We excluded the overlapping randomized controlled trials (RCTs) and performed a re-meta-analysis of the total effective rate. Results A total of eleven relevant SRs/MAs were included: nine SRs/MAs were rated critically low quality, and two were rated low quality by AMSTAR-2. According to ROBIS, all SRs/MAs were rated low risk in Phase 1 (assessing relevance) and Domain 1 (study eligibility criteria) of Phase 2. Three SRs/MAs (27.27%) were rated low risk in Domain 2 (identification and selection of studies). Ten SRs/MAs (90.91%) were rated low risk in Domain 3 (data collection and study appraisal). Five SRs/MAs (45.45%) were rated low risk in Domain 4 (synthesis and findings). And five SRs/MAs (45.45%) were rated low risk in Phase 3 (risk of bias in the review). By PRISMA 2020, there were some reporting deficiencies in the aspects of abstract (2/11, 18.18%), search strategy (0/11, 0%), preprocessing of merging data (0/11, 0%), heterogeneity exploration (6/11, 54.55%), sensitivity analysis (4/11, 36.36%), publication bias (5/11, 45.45%), evidence quality (3/11, 27.27%), the list of excluded references (3/11, 27.27%), protocol and registration (1/11, 9.09%), funding (1/11, 9.09%), conflict of interest (3/11, 27.27%), and approach to relevant information (0/11, 0%). In GRADE, the evidence quality was defined as moderate quality (8 items, 21.05%), low quality (16 items, 42.11%), and critically low quality (14 items, 36.84%). Among the downgraded factors, risk of bias, inconsistency, imprecision, and publication bias were the main factors. A re-meta-analysis revealed that manual therapy can increase the total effective rate in KOA patients (risk ratio = 1.15, 95% confidence interval [1.12, 1.18], p < 0.00001; I2 = 0, p = 0.84). There are four reviews that narratively report adverse effects, and no severe adverse reactions occurred in the manual therapy group. Conclusions Manual therapy may be clinically effective and safe for patients with KOA. However, this conclusion must be interpreted with caution because of the generally unsatisfactory study quality and inconsistent conclusions of the included SRs/MAs. Further rigorous and normative SRs/MAs are expected to be carried out to provide robust evidence for definitive conclusions. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier: CRD42022364672.